Ichthyodiversity of the five linked rivers of Chattogram, Bangladesh (Bangladesh Journal of Zoology, 2021)
Faunal records are essential to understand, manage and conserve any ecosystem if altered due to anthropogenic or natural causes. In the south eastern Bangladesh five linked rivers, Karnaphuli, Halda, Sikalbaha, Chandkhali and Sangu play a significant role in the country‟s fisheries sector. In this study ichthyofauna of the three linked rivers, Karnaphuli, Shikalbaha and Chandkhali are presented. From these three important linked rivers a total of 130 ichthyofaunal species, of which 112 finfish and 18 shellfish species were recorded during May 2010 to February 2020. Out of 130 species of finfish and shellfish, 128 species (110 fin and 18 shell fish) from the River Karnaphuli, 85 species (74 fin and 11 shell fish) from the River Shikalbaha and 83 species (72 fin and 11 shell fish) from the River Chandkhali were recorded. A total of 112 finfish species including four exotics belonged to 20 orders, 47 families, and 90 genera and 18 shellfish species were under one order, 3 families and 7 genera. Maximum finfish and shellfish species were under the families Cyprinidae (22 species) and Palaemonidae (9). Amongst the 112 finfish, one was critically endangered, six endangered and eleven was vulnerable. Systematic list of the ichthyofauna with local names is given. Status of local availability of species along with those reported as data deficient and not reported by IUCN (2015) are also provided. This study will help the fishery scientists, policy makers and planners to manage and conserve the fish faunal diversity in the three important linked rivers of Chattogram.Bangladesh J. Zool. 48(2): 215-230, 2020